OVERVIEW OF INTERIOR ELEMENTS OF ANAHATA'S HOLISTIC PSYCHOLOGY SERVICES - Damarwanti, Nuzila; Maharlika, Febry (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This research aims to examine the space-forming elements in the interior of Anahata Psychological Services with a focus on interior design that creates an environment that supports therapy and the client's psychological well-being. Qualitative research methods were used to collect data about the interior design of the Anahata psychology room. Direct observations were carried out at Anahata jl. Srisuci no. 22, Bandung City to gain an in-depth understanding of the layout, color and atmosphere of the room. Apart from that, interviews with managers and documentation related to interior design were also carried out to gain broader insight. The research results show that the interior design of Anahata's psychology room has several elements that support a conducive atmosphere for clients, such as the use of neutral colors and adjusted lighting. However, the findings also identified several shortcomings in the design, such as a lack of color and texture variation and limited ventilation systems.